Attendance Of Mass Media And Parents In Defining The Value Of Agriculture In The Eyes Of Rural (Case Study of Rural Youth at Horticulture Center in Cianjur Regency) (Lembaga Penelitian dan Pengabdian Nasyarakat Universitas Pakuan, 2017)
The scarcity of human resources in the agricultural sector or the semi-forced involvement of most of agricultural labors due to the unavailability of other alternatives, has resulted in the unoptimized production process. The young people’s attitude toward farmer as a profession and its agriculture activity is affected by three major aspects, i.e. micro aspect (parents, friends, and mass media); messo aspect (the nearby community); and macro aspect (the society). This study investigates the micro aspect in building agricultural values on young people. The study used a descriptive qulitative approach to reveal the reality of value transfer from parents and also mass media to young people in rural area. The study finds that parents particularly the father as the main actor in transferring agricultural values to young people. Television is the most accessed mass media by young people. Young people still have the interest in working in the agricultural sector, not as a main job but as a side job. Keywords: attendance of mass media and parents, value of agriculture in the eyes of rural